EIF Private Equity Mid-Market Survey 2022: Market sentiment and impact of the current geopolitical & macroeconomic environment - Helmut Krämer-Eis; Jörn Block; Antonia Botsari; Walter Diegel; Frank Lang; Davide Legnani; Solvej Lorenzen; Filip Mandys; Ioannis Tzoumas (European Investment Fund (EIF), 2022)
The EIF VC Survey, the EIF Private Equity Mid-Market Survey, and the EIF Business Angels Survey (the largest combined regular survey exercises among General Partners and Business Angels on a pan-European level) provide an opportunity to retrieve unique market insights. This publication is based on the results of the 2022 EIF Private Equity Mid-Market Survey. The paper focuses on the market sentiment as well as the impact of the current geopolitical situation and difficult macroeconomic environment. The study looks at the current situation, developments in the recent past and expectations for the future. It highlights substantial challenges, but also opportunities as perceived by survey participants. The main results are summarised and compared over time. The publication provides a valuable picture of the developments in the PE mid-market sector in 2022 as well as an outlook for the near future.
Keywords: 330